The Deeds of Philip Augustus : An English Translation of Rigord's "Gesta Philippi Augusti" - Rigord, approximately 1145-approximately 1209 (Book collections on Project MUSE., 2022)
"The first full English translation of Rigord's "Deeds of Philip Augustus" ("Gesta Philippi Augusti"), the most important narrative source for the reign of King Philip II "Augustus" of France (r. 1180-1223) and a vivid window onto many aspects of the late twelfth and early thirteenth centuries"--